Analisis Dampak Pandemi Corona Virus Disease (Covid-19) Terhadap Realisasi Pembayaran Pajak Daerah Di Kabupaten Sidoarjo - Wahyuningsih; Soesilawati Soema Atmadja (CV ODIS, 2021)
This study discusses the impact of the covid-19 pandemic on local tax payments, explaining the realization of local tax payments that declined due to covid-19. The variables of this study include the receipt of nine regional taxes, including Land and Building Tax, Land Acquisition and Land Acquisition Fees, Street Lighting Tax, Groundwater Tax, Billboard Tax, Restaurant Tax , Hotel Taxes, Entertainment Taxes, and Parking Taxes. This type of research uses explanatory research with a quantitative approach. Research location in Sidoarjo Regency Regional Tax Service Board. The data used in this study is the realization of regional financial revenues in 2018-2020. Data analysis uses descriptive techniques. The results showed that the impact of the covid-19 pandemic affected the realization of local tax payments